(untitled) (Development Service Industry Management, 2023)
The article draws attention to the problems of the state policy of ensuring the financial security of the small business sector of Ukraine in the situation of existing risks and threats of its weakening. The purpose of the study is to identify the shortcomings and problematic aspects of state policy, which lead to the activation of new challenges and threats to the financial security of the small business sector in Ukraine. The shortcomings (and their consequences) of the policy of ensuring the financial security of the small business sector in Ukraine have been identified by such management entities as central state power and management bodies, the State Regulatory Service of Ukraine, regional authorities and local self-government bodies, the system and institutions of business infrastructure, elements of business support infrastructure, management of small business entities. Prospects and directions for leveling risks and threats of weakening the financial security of the small business sector in Ukraine in conditions of instability are determined.It has been proven that a more effective and high-quality policy of strengthening the financial security of the small business sector should be aimed at eliminating such key regulatory defects in this area as: inconsistency and non-systematic planning, lack of a comprehensive long-term development program and functional and resource security of business (bodies of the central state authority); limited scope of financial and credit assistance to small business entities, small financial support and the declarative nature of business development program measures at the community level (bodies of regional authorities and local self-governments); underdevelopment of business infrastructure, especially financial resources, rural and remote areas, and the business consulting system, in particular in the field of financial and economic security of business, digitalization of business relations, critical limitation of the number and real capabilities of business incubators and business support centers, lack of institutions of support, coaching and consulting for entrepreneurs - beginners at the subregional level (corporate management systems).